What Could Represent the Mantissa of the Registered Covid-19 Cases? - Isea, Raúl (International Journal of Coronaviruses, 2022)
In this work we present how it is possible to visualize the different coronavirus outbreaks from the calculation of the mantissa from the daily record of cases by Covid-19.This curve can also indicate the speed of propagation of the disease from the calculated infection rate. These conclusions are derived from the respective calculations in four different countries: Australia, Brazil, Italy, and Venezuela.
Keywords: Mantissa; Covid-19; Infection rate; Outbreaks